Leadership Styles, Organisation Culture, and Employee Performance - Govender, Krishna Kistan (International Review of Management and Marketing, 2017)
Since poor service delivery has been linked to the inability to build a desired culture driven by inter-alia, a lack of vision and leadership, this article reports on a study which explored the above relationship by conducting a survey among a convenient cluster sample of respondents in specific public sectors in South Africa, using predeveloped and validated questionnaires. It became evident that although transformational and transactional leadership have a significant relationship with organisational culture, there was no significant correlation between “power” and “task” culture and performance. Transactional leadership showed a direct effect on employee performance, compared to transformational leadership. The implication for service delivery is that appointments to leadership positions in the South African public service should be on the basis of assessments rather than ‘comradeship.' Keywords: public sector; service delivery; performance; organizational culture; leadership JEL Classifications: L1, L2, M14